Plan de mejoramiento de los componentes de productividad y competitividad para mipymes del sector de la construcción que realizan actividades inmobiliarias, empresariales y de alquiler en el departamento del Quindío. (2014)
Recommendations. Work based on the use of surveys to analyze the various components that are part of the Model Improvement in Management and Organization locate them by stages, stage one being the lowest and four the best organizational development; Based on the above it can be said that prevailed number two, allowing you to review the problems present in this sector and in the same manner appropriate to raise such an opportunity for improvement and to achieve its budget recommendations. He threw aspects such as lack of managerial initiative to change the culture of the organization on issues related to the association, market research, economic environment, competition, exploration of new markets, implementing support tools that allow make sound decisions, incorporation of media and communication technology to provide innovation and creativity; among the most critical points highlight the issue of exports and imports, giving shows disinterest to explore different markets to the known; data showed positive human management reflecting the concern for selecting qualified personnel for the job. The relevant recommendation is training in each of these opportunities for improvement and review strategies that allow do with existing resources.